Fighting Terrorism: Empirics on Policy Harmonization - Simplice A. Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2015)
This paper models the feasibility of common policy initiatives against global terrorism, as well as timelines for their enforcement. The empirical evidence is based on 78 developing countries for the period 1984-2008. Employed terrorism dynamics are domestic, transnational, unclear and total terrorism. Absolute (or unconditional) and conditional catch-ups are modelled using Generalised Methods of Moments. We establish consistently that, the rate of catch-up is higher in domestic terrorism relative to transnational terrorism. The time to full catch-up required for the implementation of common policies without distinction of nationality is found to be in a horizon of 13.34-19.92 years for domestic terrorism and 24.67-27.88 years for transnational terrorism. Hence, from a projection date of 2009, in spite of decreasing cross-country differences in terrorists' attacks, there is still a long way to go before feasible common policy initiatives can be fully implemented without distinction of nationality. The paper is original by its contribution to the empirics of conflict resolution through decreasing cross-country differences in terrorism tendencies. Policy implications are discussed.
Keywords: C52; D74; F42; K42; O38; 330; Terrorism; Common policies; Development